Variasi Jumlah Tumbukan Terhadap Uji Karakteristik Marshall Untuk Campuran Laston (AC-BC) - Situmorang, Antonius; Pratomo, Priyo; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This study aims to determine the impact that variations in the number of collisions on thecharacteristics of the mixture laston (AC-BC) with reference to the Specifications Bina Marga,2010.This study uses a gradation on common specifications, 2010 for a mixture of Asphalt Concrete -Binder Course (AC-BC) fine gradations for middle limit and lower limit.Based on the analysis of data processing obtained that the bitumen content is used for middle limitis 6.75% and the lower limit of 7.1%. From the test results on a collision Marshall 2x55, 2x65,2x75, 2x85, 2x95 in the middle of the boundary does not meet all the parameters because the valueof Marshall Marshall Quotient (MQ) and value of voids Filled With Asphalt (VFA) did not enterthe specifications Bina Marga, 2010. While testing the limits Marshall Under the collision 2x55,2x65, 2x75, 2x85 Marshall has met all parameters. Only on collision that does not meet theparameters 2x95 Marshall because the value of Marshall Quotient (MQ) does not make anySpecification Bina Marga, 2010.Keywords : Number of CollisionsConcrete - Binder Course (AC - BC)